E-027 'Donut' aneurysm of the anterior cerebral artery: a rare vascular phenomenon. (22nd July 2019) - Strasser, S; Miskolczi, L; Azaret, C; Ionita, C; Lara, T; Lesser, M
Abstract : Introduction: Intracranial aneurysms with a 'donut-shaped' appearance are believed to be the result of laminar flow within large or giant aneurysms leading to central stagnation, intraluminal thrombosis and eventual 'donut' shaped configuration. We present a patient who experienced SAH due to ruptured 'donut' aneurysm focusing on her unique anatomy and repair. Materials and methods: A 55 year old woman presented to the ED after developing a severe headache. CT revealed left-sided SAH with the epicenter in the region of the left carotid terminus. Subsequently she was further evaluated with CTA, and catheter angiogram. Treatment with platinum coils was staged. An initial dome protection at the proposed bleeding site allowed us to further evaluate the anatomy and flow dynamics with further 2D and 3D angiograms, including a carotid cross-compression angiogram. Subsequent treatment options were flow diversion, surgical clipping and coil embolization without or with stent protection. A patent anterior communicating artery allowed us to simply coil the aneurysm resulting a sacrifice of flow via the left A1. Finally the patient was evaluated by a retinal specialist for post-treatment changes. Results: CTA and catheter angiography revealed a 25 mm donut-shaped giant aneurysm. Contrast entered via the proximal A1 and continued in a circular pattern. The outflow was separate, into the more distal A1. A Murphy's point along the superior margin of the donut represented the rupture site. Dome protection with coils at that location also disrupted the circulation of blood, reversed flow direction that now took the short route instead of the circular, long route. One week later an adequate carotid cross-compression angiogram revealed good cross-filling from right ACA to left ACA. That simplified our treatment options; the aneurysm was obliterated with coils. The left A1 segment was sacrificed. Following the procedure the patient noted 'black spots' in her vision in the left eye; neurologic exam was nonfocal; bedside acuity exam was 20/25. Retinal evaluation revealed small retinal hemorrhages in the left eye. Conclusion: Donut-shaped giant aneurysms are a rare subtype, accounting for< 1% of partially thrombosed giant aneurysms. The mechanism is proposed to be a circular, laminar flow within the aneurysm that leads to eventual central intraluminal thrombosis. In our patient the unusual feature is the separate inflow and outflow zones, separated by a 4-millimeter segment of the donut. The relationship to the optic tract remained unclear, to be further evaluated with an upcoming MRI. Our patient experienced visual symptoms shortly after final embolization and subsequently was found with several small retinal hemorrhages. How the optic nerve is associated with the aneurysm, is it possibly pinched between the aneurysm and the bony sella, or simply has some shared vascular supply, may be better determined by MRI. Disclosures: S. Strasser: None. L. Miskolczi: None. C. Azaret: None. C. Ionita: None. T. Lara: None. M. Lesser: None.